PERCEPTION: A BLACK BOX TO MARKETING? - Oliveira, Braulio; Tavares, Gracieli Regina Mendes; Sato, Karla Satiko (Revista de Administração da UFSM, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>One of the least studied elements in the marketing literature, but which is of fundamental importance for understanding the process of buying decision is perception. Thinking of perception is not only thinking about how a consumer sees their options, but also to understand the mechanisms involved in this direction. This article aims to discuss human <!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> perception from the perspective of marketing. This is a work of theoretical, with exploration goals, based on review of the literature on the subject. The stimuli are perceived by the individual through its capabilities, ie, for each individual in their personalities, mental and perceptive. It was evident the strong relationship between perception and sensory stimuli. Unravel the workings of the formation of perception can result in understanding the actions of consumers that are currently considered emotional, and fleeing the predictability of business. Studying the perception brings the ability to understand how information reaches the person and becomes conscious. The limitations of the study concern the fact and it is a test, leaving for future studies involving empirical research consistent with the issues that are worked involving perception.